2015
DOI: 10.1016/j.drugalcdep.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use among rave attendees in a nationally representative sample of US high school seniors

Abstract: Background The popularity of electronic dance music and rave parties such as dance festivals has increased in recent years. Targeted samples of party-goers suggest high rates of drug use among attendees, but few nationally representative studies have examined these associations. Methods We examined sociodemographic correlates of rave attendance and relationships between rave attendance and recent (12-month) use of various drugs in a representative US sample of high school seniors (modal age: 18) from the Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 36 publications
5
63
0
Order By: Relevance
“…A recent study focusing on a national sample of high school seniors in the US found that only 1% self-reported last-year use of “bath salts” (Palamar, 2015), and an investigation of the same national sample found that those who attend “rave” parties—especially at higher frequencies—are more likely to report “bath salt” use (Palamar et al, 2015a). Specifically, results from that study suggest that 3.7% of those ever attending a “rave” reported “bath salt” use; 6.7% of those who reported attending monthly or more often reported use, and 1.4% of those ever attending reported using “bath salts” on six or more occasions (Palamar et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study focusing on a national sample of high school seniors in the US found that only 1% self-reported last-year use of “bath salts” (Palamar, 2015), and an investigation of the same national sample found that those who attend “rave” parties—especially at higher frequencies—are more likely to report “bath salt” use (Palamar et al, 2015a). Specifically, results from that study suggest that 3.7% of those ever attending a “rave” reported “bath salt” use; 6.7% of those who reported attending monthly or more often reported use, and 1.4% of those ever attending reported using “bath salts” on six or more occasions (Palamar et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, results from that study suggest that 3.7% of those ever attending a “rave” reported “bath salt” use; 6.7% of those who reported attending monthly or more often reported use, and 1.4% of those ever attending reported using “bath salts” on six or more occasions (Palamar et al, 2015a). Findings from this current study corroborate these national survey findings in that nightclub/festival attendance was associated with a higher likelihood of having a positive test result for synthetic cathinones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, psychedelic or hallucinogen-using psychonauts and nightclub and festival attendees appear to be more drawn to NPS that have stimulant and/or psychedelic effects (31). Nightclub attendees (primarily those who prefer electronic dance music) also report high rates of NPS use compared to the general population (31,32). Our results appear to confirm associations between drugs of this type, as users of other NPS are more likely to report concomitant use of ecstasy (which is among the most common “club drugs” (17,33,34).…”
Section: Discussionmentioning
confidence: 99%